2016
DOI: 10.13189/app.2016.040201
|View full text |Cite
|
Sign up to set email alerts
|

Drug Utilization Study in Ophthalmology Outpatients in a Tertiary Care Hospital

Abstract: Aims: The present study was carried out to describe the patterns of prescription and drug use in Ophthalmology outpatients at GG hospital, Jamnagar, Gujarat, India. Methods: Total of 600 patients were included during 3 months duration and average number of drugs per encounter, percentage of drugs prescribed by generic name, percentage of encounters with antibiotics prescribed, percentage of encounters with an injection prescribed, percentage of drugs prescribed from the WHO Essential Drug List 2015, number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
2
3
1
Order By: Relevance
“…In the present study, the percentage of drugs prescribed from essential drug list was 61.4% which is lower than the ideal WHO value. In various studies, values lower than those in our study have been reported (25,26).…”
Section: In This Retrospective Analysis Of Patient Data From the Obesity Outpatient Clinic Of Istanbul Medeniyet University Goztepe Traincontrasting
confidence: 84%
See 1 more Smart Citation
“…In the present study, the percentage of drugs prescribed from essential drug list was 61.4% which is lower than the ideal WHO value. In various studies, values lower than those in our study have been reported (25,26).…”
Section: In This Retrospective Analysis Of Patient Data From the Obesity Outpatient Clinic Of Istanbul Medeniyet University Goztepe Traincontrasting
confidence: 84%
“…Low antibiotic use rate could be related to the type of outpatient clinic, namely similar to our results, very low rates of antibiotic use were reported from diabetes outpatient settings in South-Eastern Nigeria (1.7%) and Nepal (0.88%), (24,25). Conversely, high rates of antibiotic use were reported by a study conducted at ophthalmology outpatient clinic in India (62.2%) (26).…”
Section: In This Retrospective Analysis Of Patient Data From the Obesity Outpatient Clinic Of Istanbul Medeniyet University Goztepe Trainmentioning
confidence: 90%
“…Other similar studies in ophthalmology in India have reported 30%-45% encounters with antibiotics which is lower than our study. 14,15 Fluoroquinolones were the most common group of antibiotics prescribed which were similar to reports of previous studies done in ophthalmology. 13,14,15 Ciprofloxacin 0.3% as drops and ointment is included in National List of Essential Medicines 2015, deemed to be available at Primary, Secondary and Tertiary levels of health care and hence preferred in many prescriptions as patients could use them free of cost.…”
Section: Generic Namesupporting
confidence: 80%
“…Around 86% patients had encounters with an antibiotic prescribed, which was higher compared to studies done by Vanya HV et al 13 and Bhatt JH et al 23 which showed lower values (62.2%, 32.6%). It may be due to poor sanitation in our area which leads to higher prevalence of the infective diseases of the eyes, poor education, dry environment and less awareness.…”
Section: Discussionmentioning
confidence: 55%
“…12 In India, literature studies in Ophthalmology had shown issues of poor selection and prescribing of essential drugs and generic medicines. 13 Keeping these facts in consideration, the study was intended to obtain knowledge on the prescribing pattern and drug utilization trend in ophthalmology department at a tertiary care teaching hospital with ultimate goal to promote rational use of drugs among prescribers.…”
Section: Introductionmentioning
confidence: 99%